3D In vitro model of the re‐epithelialization phase in the wound‐healing process. Issue 5 (14th August 2017) - Deshayes, Nathalie; Bloas, Fabienne; Boissout, Florian; Lecardonnel, Jennifer; Paris, Maryline
Abstract: Keratinocytes of the basal layer function are to maintain tissue homoeostasis and to fulfil skin repair in response to an external aggression. In wound‐healing, during re‐epithelialization phase, epithelial precursor cells gradually migrate from the edges of the wound. The epidermal reconstruction model called standard model allows the vertical skin regeneration process (proliferation/differentiation) to being investigated, and keratinocyte function in preserving skin homoeostasis to being assessed. Here, we developed and characterized a 3D migration model, which introduces a step of keratinocytes migration such as the one observed in the phase of re‐epithelialization in wound‐healing process. We validated the added value and the discriminative potential of this model by demonstrating pro‐epithelializing effects of compounds. This new model allows the role of keratinocytes in different biomechanical and environmental requests to being better understood, and brings a new tool for compound screening and the study of mechanisms involved in skin regeneration.